1992
DOI: 10.7326/0003-4819-117-11-898
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Persistent Dizziness

Abstract: Vestibular disease and psychiatric disorders are the most common causes of persistent dizziness in outpatients. In about 50% of patients with dizziness, more than one factor causes or aggravates symptoms. Life-threatening causes were rare, even in our elderly population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0
4

Year Published

1993
1993
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(58 citation statements)
references
References 25 publications
4
50
0
4
Order By: Relevance
“…This finding is congruent with research (e.g., Kroenke et al, 1992;Sullivan et al, 1993) that has found a large percentage of dizzy patients to have psychiatric diagnoses or psychological symptoms or that psychiatric and autonomic symptoms are more important diagnostically than dizziness quality (Clark et al, 1994). These findings point to the importance of psychosocial factors in the assessment and treatment of the dizzy patient.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This finding is congruent with research (e.g., Kroenke et al, 1992;Sullivan et al, 1993) that has found a large percentage of dizzy patients to have psychiatric diagnoses or psychological symptoms or that psychiatric and autonomic symptoms are more important diagnostically than dizziness quality (Clark et al, 1994). These findings point to the importance of psychosocial factors in the assessment and treatment of the dizzy patient.…”
Section: Discussionsupporting
confidence: 87%
“…As many as 80% of patients with dizziness seen in a general outpatient clinic go undiagnosed, and there is a high prevalence of unrecognized mood and psychiatric problems in dizzy patients (Sullivan et al, 1993). In one multidisciplinary study, psychiatric disorders were diagnosed in 40% of the dizzy patients seen (Kroenke et al, 1992). Clark et al (1994) found that autonomic and psychiatric questionnaire items were more useful in classifying dizzy patients according to the presence or absence of a peripheral vestibular disorder or a psychiatric disorder than dizziness symptoms like vertigo and lightheadedness.…”
Section: Introductionmentioning
confidence: 99%
“…These findings match other reports on the pivotal diagnostic contribution of careful history taking and physical examination alone in various patient populations. 1,[4][5][6][7][8][11][12][13]22 Medical practitioners often rely on experience and feelings that are described as "probable" or "undoubted." Here we provide some evidence concerning the adequacy of such terms in the context of nonorganic versus organic abdominal and chest pain.…”
Section: Discussionmentioning
confidence: 99%
“…1 An extensive workup in patients with abdominal or chest pain suspected of having nonorganic causes may identify only a few patients with organic causes and may therefore have a very low diagnostic yield. [4][5][6][7][8] This suggests that additional and sometimes costly investigations might be unnecessary. 1,5,[9][10][11][12][13] There are a few studies on the diagnostic accuracy of physicians' initial assessments of nonorganic versus organic diagnoses in patients with abdominal or chest pain in primary care.…”
mentioning
confidence: 99%
“…Among these, a variety of diagnoses are represented, most of them benign, whereas life-threatening conditions are rare [2]. Dizziness can originate from peripheral structures, have a central origin or can be caused by other diseases such as multiple sensory deficits or cardiac disease [3].…”
mentioning
confidence: 99%